Measurement of the energy density as a function of pseudorapidity in proton-proton collisions at root s=13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (10.1140/epjc/s10052-019-6861-x, 2019)
A measurement of the energy density in proton– proton collisions at a centre-of-mass energy of √s = 13 TeV is presented. The data have been recorded with the CMS experiment at the LHC during low luminosity operations in 2015. The energy density is studied as a function of pseudorapidity in the ranges − 6.6 <η< − 5.2 and 3.15 < |η| < 5.20. The results are compared with the predictions of several models. All the models considered suggest a different shape of the pseudorapidity dependence compared to that observed in the data. A comparison with LHC proton–proton collision data at √s = 0.9 and 7 TeV confirms the compatibility of the data with the hypothesis of limiting fragmentation.